2020
DOI: 10.5415/apallergy.2020.10.e40
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ knowledge regarding epinephrine underuse in anaphylaxis

Abstract: Background: Anaphylaxis is a life-threating hypersensitivity reaction. Epinephrine underuse in patients with anaphylaxis could lead to poor outcomes. There is evidence that the epinephrine use in such patients could be as low as 8%. Objective: To assess the percentage of physicians who know that epinephrine is the first-line treatment in anaphylaxis. The secondary objective was to assess knowledge gaps regarding anaphylaxis diagnosis and treatment that could lead to epinephrine underuse. Methods: We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Our study, including healthcare professionals from different healthcare institutions, showed that there was a lack of knowledge among healthcare professionals regarding the acute treatment of anaphylaxis such as the dose of epinephrine, and long-term therapy such as EAI doses, and prescribing rates. This lack of knowledge was similar to previous studies conducted in Turkey and different countries [ 16 17 18 19 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study, including healthcare professionals from different healthcare institutions, showed that there was a lack of knowledge among healthcare professionals regarding the acute treatment of anaphylaxis such as the dose of epinephrine, and long-term therapy such as EAI doses, and prescribing rates. This lack of knowledge was similar to previous studies conducted in Turkey and different countries [ 16 17 18 19 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pimental et al 20 reported 196 specialist physicians: pediatrics, internal medicine, cardiology, anesthesiology, general surgery, orthopedics, and gynecology. In 72.4% of the physicians, they responded that adrenaline is the first line of treatment, intramuscular route in 64.3%, correct dose in 50%; while other studies report that 70.9% of healthcare providers do not know the correct dose in an acute episode of anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the other hand, our colleagues from MGH have identified how untrained non-allergist staff fails to identify and treat anaphylaxis adequately even when consciously subjecting patients to high-risk allergy-specific procedures like intravenous DPT, 47,95 which is consistent with the published experience in anaphylaxis whether in the community or the hospital. [101][102][103][104][105][106] Creating a multidisciplinary team…”
Section: The Shared Unique Selling Proposition Among Leading Groups I...mentioning
confidence: 99%